Public-private partnerships in the real estate sector in Colombia :risk assessment matrix and risk allocation proposal = Asociaciones público privadas en el sector inmobiliario en Colombia : una propuesta de matríz y asignación de riesgos (2017)
The implementation of Public-Private Partnerships in infrastructure projects in Colombia has proven to be an efficient and innovative opportunity in the execution and management of projects that contribute to the development of the country. As expected, the increase in the use of these associations in infrastructure encourages other sectors to carry out their projects under the same figure. Currently, in the real estate sector, some projects that seek to maximize their benefits and mitigate their risks through the experience of the public entity and the private companies are under study, or in the structuring or execution phase. However, given its recent application, the real estate sector does not have a risk matrix to guide its parties regarding the risks each must assume. In this work, a first model of this matrix is constructed for the case of Colombia. This model will be supported by research from various national and international sources and studies. Additionally, based on the found information, an identification of the most frequent risks and those responsible for their prevention and mitigation are assigned. This process allowed us to conclude that the existing matrix used in the PPPs of the real estate sector in Colombia is very general and, therefore, does not consider several evident risks like for example political, those that consider the relationship between the involved parties and the residual risk. For risk allocation, it is proposed the public sector to be responsible for political risks and at least for most of the legal risks. In the case of technical, market and general project management risks, the private sector must assume the higher percentage. Finally, social and environmental / natural risks must enter negotiation to be assigned to the party that best manage them and at a lower cost